High Spatial Inhomogeneity in the Intima-Media Thickness of the Common Carotid Artery is Associated with a Larger Degree of Stenosis in the Internal Carotid Artery: The PARISK Study - Steinbuch, Jeire; van Dijk, Anouk C.; Schreuder, Floris H. B. M.; Truijman, Martine T. B.; de Rotte, Alexandra A. J.; Nederkoorn, Paul J.; van der Lugt, Aad; Hermeling, Evelien; Hoeks, Arnold P. G.; Mess, Werner H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose Inhomogeneity of arterial wall thickness may be indicative of distal plaques. This study investigates the intra-subject association between relative spatial intima-media thickness (IMT) inhomogeneity of the common carotid artery (CCA) and the degree of stenosis of plaques in the internal carotid artery (ICA).Materials and Methods We included 240 patients with a recent ischemic stroke or transient ischemic attack and mild-to-moderate stenosis in the ipsilateral ICA. IMT inhomogeneity was extracted from B-mode ultrasound recordings. The degree of ICA stenosis was assessed on CT angiography according to the European Carotid Surgery Trial method. Patients were divided into groups with a low (≤ 2 %) and a high (> 2 %) IMT inhomogeneity scaled with respect to the local end-diastolic diameter.Results 182 patients had suitable CT and ultrasound measurements. Relative CCA-IMT inhomogeneity was similar for the symptomatic and asymptomatic side (difference: 0.02 %, p = 0.85). High relative IMT inhomogeneity was associated with a larger IMT (difference: 235 µm, p < 0.001) and larger degree of ICA stenosis (difference: 5 %, p = 0.023) which remained significant (p = 0.016) after adjustment for common risk factors.Conclusion Regardless of common risk factors, high relative CCA-IMT inhomogeneity is associated with a greater degree of ICA stenosis and is therefore indicative of atherosclerotic disease. The predictive value of CCA-IMT inhomogeneity for plaque progression and recurrence of cerebrovascular symptoms will be determined in the follow-up phase of PARISK.
Keywords: carotid arteries; ultrasound 2 D; arteriosclerosis; IMT inhomogeneity; stroke/TIA